BANARAN LESTARI VILLAGE: INTEGRASI POTENSI WISATA DAN PENGUATAN MANAJEMEN PARIWISATA BERBASIS COMMUNITY-BASED TOURISM DALAM MEWUJUDKAN PARIWISATA BAHARI BERKELANJUTAN DI DESA BANARAN - Lesmana, Indra; Mauliddya, Koriq Nur; Al Huda, Ahmad Zaki; Kususmatuti, Dissa; Lambang, Muhmammad Aryo; Mujahid, Syariful; Saputra, Fadil Nur Muhamad; Putri, Nabila Ihsani; Fathonah M.S, Indriyani; Putri, Bina Sabina; Fridayani, Helen Dian (Universitas Muhammadiyah Yogyakarta, 2026)
Banaran Village, located in Galur District, Kulon Progo Regency, has marine tourism potential through Trisik Beach, Trisik Lagoon, and a sea turtle conservation area. However, tourism development still faces interconnected environmental and institutional issues, including plastic waste and coastal pollution, shoreline abrasion threatening turtle habitats and mangrove ecosystems, limited tourism facilities, low availability of tourism information and digital promotion, and suboptimal management of the tourism awareness group (Pokdarwis) and MSME empowerment. This community service program under the Young Sustainable Initiative (YSI) KOMAP UMY was designed to integrate tourism potential with strengthened tourism management based on the Community-Based Tourism (CBT) approach to support sustainable marine tourism development in Banaran Village. The program applied a participatory method through problem identification, socialization and counseling, training and education, field practices, mentoring, and Focus Group Discussions (FGD) for evaluation. The activities included strengthening Pokdarwis institutional capacity (Grow Together), developing branding and digital marketing (Smart Tour Banaran), coastal conservation (Save Nature Save Future), improving tourism facilities (Mantra Wisata), empowering MSMEs (Banaran Entrepreneur), and plastic waste management through upcycling activities. The results showed high community participation (85-93%) and improvements in institutional capacity, digital promotion skills, supporting tourism facilities, increased conservation awareness, and the creation of upcycled products with economic value. The program strengthened collaboration among students, village government, Pokdarwis, MSMEs, and the community, contributing to environmental quality improvement and local economic development as foundations for the sustainability of Banaran’s marine tourism.